2014
DOI: 10.20885/jsb.vol17.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Praktik pengungkapan sosial: Studi komparatif di Asia Tenggara

Abstract: This research aims to examine the effect of corporate governance on the corporate social disclosure in the South East Asia companies as well as to test the difference of the level of corporate social disclosure (CSD) between three countries: Indonesia, Malaysia, and Thayland. Variables in the research are: the number of commissioners, board competence, the proportion of independent commissioners, audit committee size, the proportion of independent audit committees, and ownership of managerial. Global Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…Suttipun &Stanton (2012), Sembiring (2005), Purwanto (2011), dan Solikhah & Winarsih (2016) menemukan hasil bahwa tipe industri berpengaruh signifikan terhadap pengungkapan lingkungan, namun hasil berbeda ditemukan oleh Fauzi, Mahoney & Rahman (2007). Supriyono & Suhardjanto (2013), Yanti & Rasmini (2015), Rahmawati & Budiwati (2018) telah melakukan penelitian terkait perbedaan pengungkapan lingkungan di dua negara atau lebih.…”
Section: Pendahuluanunclassified
“…Suttipun &Stanton (2012), Sembiring (2005), Purwanto (2011), dan Solikhah & Winarsih (2016) menemukan hasil bahwa tipe industri berpengaruh signifikan terhadap pengungkapan lingkungan, namun hasil berbeda ditemukan oleh Fauzi, Mahoney & Rahman (2007). Supriyono & Suhardjanto (2013), Yanti & Rasmini (2015), Rahmawati & Budiwati (2018) telah melakukan penelitian terkait perbedaan pengungkapan lingkungan di dua negara atau lebih.…”
Section: Pendahuluanunclassified
“…The three countries also adopt different systems in the implementation of corporate governance. Indonesia adheres to the Two-Tier System, Malaysia adheres to the One Tier System system while Thailand does not clearly adhere to which system of the two systems (Supriyono & Suhardjanto, 2014).…”
Section: Literature Studymentioning
confidence: 99%
“…Similarly, environmental disclosure in Southeast Asian countries such as Indonesia, Malaysia, and Thailand. Research conducted by Supriyono & Suhardjanto (2014) in three Southeast Asian countries namely Indonesia, Malaysia, and Thailand revealed that there are differences in corporate social disclosure practices in Southeast Asia caused by corporate governance practices.…”
Section: Literature Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A larger proportion of independent commissioners will encourage management to disclose voluntary information, among them social disclosure. Supriyono (2013) state that a heavy audit committee requires not only the ability but also the amount sufficient to be optimal in performing their duties. The greater the number of audit committees the more effective they will be in overseeing the quality of financial statement disclosure, including CSD.…”
Section: Introductionmentioning
confidence: 99%